Learning ecosystem for higher education disruption: A new approach proposal based on blended active learning techniques - Moreira, Fernando (2018)
The paradigm in higher education is changing due to the pressure imposed on the one hand by the new technologies and on the other by the characteristics (habits and skills) presented by the students who arrive at the universities. These characteristics are not compatible with the teaching methodologies used up until the present, the traditional model (lectures) consolidated in the nineteenth century. Thus, teachers using active learning have attracted much attention because they stimulate motivation and autonomy to achieve more competencies on the part of the students and are aligned with the guidelines, for example the European Standards and Guidelines for Quality in Higher Education. In order to respond to these new challenges, an innovative pilot project was developed, from the pedagogical point of view, implemented in a 1st Cycle course (Management and Information Systems) and using various active methodologies. In this context, a model composed of three Active Learning techniques (Group Project, Peer Review and Peer Teaching) was developed and implemented within the framework of the “New Tendencies in ITs” course, 1st semester, 2nd year, called ECLECTIC approach. The results obtained are very promising, because they have allowed students to engage in and out of the classroom and have resulted in an approval rate of more than 80%.